CHEMOKINE RECEPTORS - Gibejova, Agata (Biomedical papers, 2000)
Chemokines mediate their multiple effects by binding to a variety of specific receptors, that comprise a subfamilyof rhodopsin-like, 7-transmembrane domain receptors, coupled to G proteins. Some of these receptors serve ascoreceptors for HIV, some of them could be expressed as markers for T lymphocyte functional differentiation. Thisreview aims at summarising data on chemokine receptors, their function in vivo, their target cells and it alsomentions association of chemokine receptor polymorphisms with human disease.
Keywords: Chemokines / Chemokine receptors / Polymorphisms / Knockout mice / Function in vivo